Entangling the Motion of Diamonds at Room Temperature - Sprague, MR; Lee, K; Sussman, B; Nunn, J; Langford, N; Jin, X; Champion, T; Michelberger, P; Reim, K; England, D; Jaksch, D; Walmsley, I; et al. (2012)
We demonstrate entanglement between the vibrational mode of two macroscopic, spatially-separated diamonds at room temperature with ultrashort pulses and a far-off-resonant Raman interaction. © 2012 OSA.